Sanksi Ekonomi Amerika Serikat Terhadap Iran Pada Masa Pandemi Covid-19 (Coronavirus Disease 2019) - Meyland S.F. Wambrauw; Mathius Apintamon (Papua Journal of Diplomacy and International Relations, 2021)
This study examines why the United States (US) imposes economic sanctions against Iran during the Covid-19 pandemic and the impacts on the ongoing tensions between the two countries. By adopting qualitative descriptive analysis, the study found that the US enforced a series of economic sanctions on Iran because it was considered a threat to US economic and strategic interests in the region. Not only did the US apply sanctions on foreign-affiliated companies assisting Iranian people's health services due to the indication of financing of terrorism, but the US also blacklisted several Iranian officials for human rights violations. The US even convinced the IMF not to provide 'emergency loan funds' to Iran. As a consequence, Iran found it difficult to get access to medicines and medical equipment which was fundamentally important to fight the outbreak of the Covid-19. Iran previously struggled with US economic sanctions, and the further sanctions during the Covid-19 had exacerbated the country's situation. It is also worth noting that the US, in this context, ignored the aspect of human life in Iran because of its sanctions during the Covid-19 pandemic.KEYWORDSCovid-19; Iran; Sanctions; United States